Artificial Intelligence in healthcare: Problems and prospects of ethical and legal regulation - Anishchenko, M. A.; Filei, Yu. V.; Prasov, O. O.; Kornieiev, Yu. V.; Shkabaro, V. N.; Аніщенко, Михайло Анатолійович (My University, 2024)
The main problems and prospects for ethical and legal regulation of artificial intelligence in the field of healthcare have been researched. It has been stated that artificial intelligence is one of the promising directions in medicine, its implementation will make it possible to analyze significant amounts of information about patients from different databases, which, as a result, will contribute to both saving time and the accuracy and timeliness of prescribing or adjusting treatment. The issues of the legal nature of artificial intelligence, the main legislative acts at the national and international level, which regulate activities in this direction, have been considered. The European Union (EU) draft of Artificial Intelligence Act, which provides for the classification and regulation of an artificial intelligence program based on its potential risk, has been analyzed, its main tasks and requirements for EU member states have been outlined. It has been found that Ukraine is also taking part in the implementation of this bill (the sandbox regulator ―was launched‖, a working group on the legal regulation of artificial intelligence was created in the National Bar Association of Ukraine). The issues of legal personality of artificial intelligence, protection of the right to privacy in the process of functioning and operation of artificial intelligence have been considered. The basic ethical principles of using artificial intelligence in medicine and the main legal aspects of introducing artificial intelligence into the healthcare system have been determined. Attention is focused on the need to regulate native legislation that governs activities in this field, because namely the lack of clear legal regulation of these issues contributes to both rapid technological development in this direction and the emergence of risks that will be accompanied in connection with its popularization.
Keywords: artificial intelligence; medicine; legislation; ethical principles; protection of the right to privacy; databases